The socio-economic benefits of tidal power to the European economy (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The International Energy Agency’s technology collaboration programme on Ocean Energy Systems (IEA-OES) has published a roadmap to deploy 300 GW of ocean energy globally by 2050, with an associated $340bn in Gross Value Added (GVA) and 680,000 Full-Time Equivalent (FTE) jobs [1]. This roadmap includes a global target for 120 GW of tidal stream power by 2050.To complement the IEA-OES high-level analysis, this paper will investigate for the first time the value of tidal stream to the European economy with country and technology specific case studies. Conducted as part of the Horizon2020 funded FORWARD2030 project led by Orbital Marine Power, the analysis incorporates the latest economic Input-Output tables, to reflect recent changes in markets and industrial sectors. It builds on previous work [2–4], using more detailed project and technology assumptions, informed by experience from Orbital and other sources. Varying levels of supply chain retention and European competitiveness are considered. Finally, the technology deployment trajectory is guided by recent successes for commercial tidal stream projects in the UK and elsewhere.The economic benefits resulting from developing, building & operating tidal stream projects are modelled. They are quantified using two common metrics, GVA and FTE jobs. Preliminary results show that the economic benefit of building and installing 6.2 GW of tidal stream capacity in the UK by 2050 could result in almost £5.8bn (€6.9bn) in GVA and result in over 7800 FTE jobs in 2050. The potential export market is also explored, as this could be even more significant.Results will be presented for a range of scenarios of market share and supply chain retention, broken down by project stage and industrial sectors. The preliminary results also show that device construction is the biggest share, making up over half the jobs in the medium term. By 2050, the operation & maintenance of turbines and farms could be more than a quarter of all jobs in the tidal stream sector. A significant proportion of the jobs are in the manufacturing sector, offering the opportunity for transfer of skilled workforce from the oil & gas and other sectors as part of the Just Transition.This work will present a unique set of results on the opportunities for the tidal stream sector and its supply chain. It will be of interest both to the scientific community and to European, country and regional policymakers.References[1]       IEA-OES, ‘Ocean Energy and Net Zero: An International Roadmap to Develop 300GW of Ocean Energy by 2050’, 2023.[2]       D. R. Noble, K. Grattan, and H. Jeffey, ‘Future economic potential of Tidal Stream & Wave Energy in Scotland’, The University of Edinburgh, 2025. (in press)[3]       C. Cochrane, S. Pennock, and H. Jeffrey, ‘A study into the potential economic value offered to Europe from the development and deployment of wave and tidal energy to 2050’, ETIP Ocean, 2021[4]       C. Cochrane, S. Pennock, and H. Jeffrey, ‘What is the value of innovative offshore renewable energy deployment to the UK economy?’, Supergen ORE, 2021.